Outcomes after repeat hepatectomy for colorectal liver metastases from the colorectal liver operative metastasis international collaborative (COLOMIC). Issue 7 (15th August 2022) - Valenzuela, Cristian D.; Moaven, Omeed; Gawdi, Rohin; Stauffer, John A.; Del Piccolo, Nico R.; Cheung, Tan To; Corvera, Carlos U.; Wisneski, Andrew D.; Cha, Charles; Pourhabibi Zarandi, Nima; Dourado, Justin; Perry, Kathleen C.; et al.
Abstract: Background: Resection of colorectal liver metastasis (CLM) is beneficial when feasible. However, the benefit of second hepatectomy for hepatic recurrence in CLM remains unclear. Methods: The Colorectal Liver Operative Metastasis International Collaborative retrospectively examined 1004 CLM cases from 2000 to 2018 from a total of 953 patients. Hepatic recurrence after initial hepatectomy was identified in 218 patients. Kaplan–Meier analysis was performed for overall survival (OS) and recurrence‐free survival (RFS). Propensity score matching (PSM) was performed to offset selection bias. Cox proportional‐hazards regression was performed to identify risk factors associated with OS. Results: A total of 51 patients underwent second hepatectomy. Unadjusted median OS was 60.1 months in repeat‐hepatectomy versus 38.3 months in the single‐hepatectomy group ( p = 0.015). In the PSM population, median OS remained significantly better in the repeat‐hepatectomy group (60.1 vs. 33.1 months; p = 0.0023); median RFS was 12.4 months for the repeat‐hepatectomy group, versus 9.8 months in the single‐hepatectomy group ( p = 0.0050). Repeat hepatectomy was associated with lower risk of death (hazard ratio: 0.283; p = 0.000012). Obesity, tobacco use, and high intraoperative blood loss were associated with significant risk of death ( p < 0.05). Conclusion: In CLM with hepatic recurrence, second hepatectomy was beneficial for OS. With PSM, the OS benefit of performing a second hepatectomy remained significant.